Who Are You? On Being Half Indian and Half White (LEARNing Landscapes, 2014)
Coming from a mixed ethnic identity is difficult, particularly if the two identities of which you are mixed look physically very different. Through personal narratives, the author makes visible how one’s appearance can determine how other people interpret one’s identity. She examines challenges that arise when the messages one receives about one’s identity are contradictory and relates these contradictory messages to the concept of social dominance. The author makes it apparent that place and community establish one’s feelings about oneself. She concludes that an individual of mixed race cannot extract one ethnicity from the other; the individual will always be both.
Keywords: identity; inclusion; mixed ethnicity; narrative; appearance; social dominance; place; community